Adverse drug events in patients admitted to an emergency department: an analysis of direct costs - Meier, Florian; Maas, Renke; Sonst, Anja; Patapovas, Andrius; Müller, Fabian; Plank-Kiegele, Bettina; Pfistermeister, Barbara; Schöffski, Oliver; Bürkle, Thomas; Dormann, Harald (Pharmacoepidemiology and Drug Safety, 2015)
Purpose Several economic evaluations of adverse drug events (ADEs) exist, but the underlying methodology has not been standardized so far. The aim of the study was to combine prospective, intensive pharmacovigilance methods, and standardized accounting data to calculate direct costs of community-acquired ADEs (caADEs) contributing to emergency department (ED) admission and subsequent hospitalization. Methods A prospective observational study with three phases extending over 2 years was implemented in a 749 bed tertiary care hospital with an annual ED census of approximately 45 000 patients. The patient records of all adult non-trauma ED admissions were systematically analyzed by a team of emergency physicians, clinical pharmacologists, and pharmacists for potential ADE. Associated diagnosis related group costs were extracted from standardized accounting data. Results Of 2262 patients attending the ED during the study periods, the hospitalization of 366 patients (16.2%) was related to one or more caADEs of which 97.5% were considered predictable and 62.0% were classified as preventable. The mean caADE-related diagnosis related group costs were €2743 (95% bias-corrected and accelerated CI: €2498 to €3018). Extrapolated to a national scale, this corresponds to caADE-related costs of €2.245bn for the German health insurance funds, annually. Costs of €1.310bn could be attributed to events classified as predictable and preventable. Conclusions In an ED, caADEs are frequent, and a significant proportion of these events and their related costs appear to be predictable and preventable. The ED as a first-line provider for ADE cases appears to be an appropriate environment to implement strategic and operative improvements for enhanced patient safety.
Keywords: adverse drug event; hospital admission; emergency department; pharmacovigilance; health economics; pharmacoepidemiology

Application of the Pareto principle to identify and address drug-therapy safety issues - Müller, Fabian; Dormann, Harald; Pfistermeister, Barbara; Sonst, Anja; Patapovas, Andrius; Vogler, Renate; Hartmann, Nina; Plank-Kiegele, Bettina; Kirchner, Melanie; Bürkle, Thomas; Maas, Renke (European Journal of Clinical Pharmacology, 2014)
Adverse drug events (ADE) and medication errors (ME) are common causes of morbidity in patients presenting at emergency departments (ED). Recognition of ADE as being drug related and prevention of ME are key to enhancing pharmacotherapy safety in ED. We assessed the applicability of the Pareto principle ( 80 % of effects result from 20 % of causes) to address locally relevant problems of drug therapy.In 752 cases consecutively admitted to the nontraumatic ED of a major regional hospital, ADE, ME, contributing drugs, preventability, and detection rates of ADE by ED staff were investigated. Symptoms, errors, and drugs were sorted by frequency in order to apply the Pareto principle.In total, 242 ADE were observed, and 148 (61.2 %) were assessed as preventable. ADE contributed to 110 inpatient hospitalizations. The ten most frequent symptoms were causally involved in 88 (80.0 %) inpatient hospitalizations. Only 45 (18.6 %) ADE were recognized as drug-related problems until discharge from the ED. A limited set of 33 drugs accounted for 184 (76.0 %) ADE; ME contributed to 57 ADE. Frequency-based listing of ADE, ME, and drugs involved allowed identification of the most relevant problems and development of easily to implement safety measures, such as wall and pocket charts.The Pareto principle provides a method for identifying the locally most relevant ADE, ME, and involved drugs. This permits subsequent development of interventions to increase patient safety in the ED admission process that best suit local needs.
EVALuna2:123

Case-based visualization of a patient cohort using SEER epidemiologic data - Maier, Christian; Bürkle, Thomas; Prokosch, Hans-Ulrich; Ganslandt, Thomas (Studies in health technology and informatics, 2014)
Data from cancer registries can be used to track the epidemiology of cancer and can potentially serve to guide individual diagnostic and treatment decisions. Even though some cancer registry datasets have been made publicly available for scientific and clinical use, few applications have so far provided direct access to these data from within the patient context of an electronic patient record. The goal of this project was to implement a proof-of-concept integration of the public SEER (Surveillance, Epidemiology and End Results) cancer registry dataset with a digital breast cancer tumor board at a German university hospital and to determine its utility in the clinical settings. The integration was successfully established, using data from routine documentation to provide dynamic visualizations of cohort composition and Kaplan-Meier survival plots. Evaluation feedback was favorable regarding the concept and implementation, but highlighted that important data elements, e.g. receptor status data, were missing in the SEER dataset, limiting clinical value of the system.
EVALuna2:119

Data requirements for the correct identification of medication errors and adverse drug events in patients presenting at an emergency department - Plank-Kiegele, Bettina; Bürkle, Thomas; Müller, Fabian; Patapovas, Andrius; Sonst, Anja; Pfistermeister, Barbara; Dormann, Harald; Maas, Renke (Methods of Information in Medicine, 2017)
EVALuna2:34049
Keywords: Adverse drug event; Clinical decision support system; Medication data; Medication error; Prospective study; Side effect

Identifying barriers for implementation of computer based nursing documentation - Vollmer, Anne-Maria; Prokosch, Hans-Ulrich; Bürkle, Thomas (Studies in health technology and informatics, 2014)
This study was undertaken in the planning phase for the introduction of a comprehensive computer based nursing documentation system at Erlangen University Hospital. There, we expect a wide range of difficult organizational changes, because the nurses currently neither used computer based nursing documentation nor did they follow strongly the nursing process model within paper based documentation. Thus we were eager to recognize potential pitfalls early and to identify potential barriers for digital nursing documentation. In a questionnaire study we surveyed all German university hospitals for their experience with the implementation of computer based nursing documentation implementation. We received answers from 11 of the 23 hospitals. Furthermore we performed a questionnaire study about expectations and fears among the nurses of four pilot wards of our hospital. Most respondents stated a positive attitude towards the nursing process documentation, but many respondents note technical (e.g. bad performance of the software) and organizational barriers (e.g. lack of time).
EVALuna2:118

Implementation of a patient data management system : Effects on intensive care documentation - Castellanos, Ixchel; Ganslandt, Thomas; Prokosch, Hans-Ulrich; Schüttler, Jürgen; Bürkle, Thomas (Anaesthesist, 2013)
Patient data management systems (PDMS) enable digital documentation on intensive care units (ICU) and have positive effects on completness, quality and quantity of documented information. A commercial PDMS was implemented in a 25-bed ICU replacing paper-based patient charting. The ICU electronic patient record is completely managed inside the PDMS. IT compiles data from vital signs monitors, ventilators and further medical devices and facilitates some drug dose and fluid balance calculations as well as data reuse for administrative purposes. Ventilation time and patient severity scoring as well as coding of diagnoses and procedures is supported. Billing data transferred via interface to the central billing system of the hospital. Such benefits should show in measurable parameters, such as documented ventilator time, number of coded diagnoses and procedures and others. These parameters influence reimbursement in the German DRG system. Therefore, measurable changes in cost and reimbursement data of the ICU were expected.A retrospective analysis of documentation quality parameters, cost data and mortality rate of a 25-bed surgical ICU within a German university hospital 3 years before (2004-2006) and 5 years after (2007-2011) PDMS implementation. Selected parameters were documented electronically, consistently and reproducibly for the complete time span of 8 years including those years where no electronic patient recording was available. The following parameters were included: number of cleared DRG, cleared ventilator time, case mix (CM), case mix index (CMI), length of stay, number of coded diagnoses and procedures, detailed overview of a specific procedure code based on daily Apache II and TISS Core 10 scores, mortality, total ICU costs and revenues and partial profits for specific ICU procedures, such as renal replacement therapy and blood products.Systematic shifts were detected over the study period, such as increasing case numbers and decreasing length of stay as well as annual fluctuations in severity of disease seen in the CM and CMI. After PDMS introduction, the total number of coded diagnoses increased but the proportion of DRG relevant diagnoses dropped significantly. The number of procedures increased (not significantly) and the number of procedures per case did not rise significantly. The procedure 8-980 showed a significant increase after PDMS introduction whereas the DRG-relevant proportion of those procedures dropped insignificantly. The number of ventilator-associated DRG cases as well as the total ventilator time increased but not significantly. Costs and revenues increased slightly but profit varied considerably from year to year in the 5 years after system implementation. A small increase was observed per case, per nursing day and per case mix point. Additional revenues for specific ICU procedures increased in the years before and dropped after PDMS implementation. There was an insignificant increase in ICU mortality rate from 7.4 % in the year 2006 (before) to 8.5 % in 2007 (after PDMS implementation). In the following years mortality dropped below the base level.The implementation of the PDMS showed only small effects on documentation of reimbursement-relevant parameters which were too small to set off against the total investment. The method itself, a long-term follow-up of different parameters proved successful and can be adapted by other organizations. The quality of results depends on the availability of long-term parameters in good quality. No significant influence of PDMS on mortality was found.
EVALuna2:113

Inconsistencies and misleading information in officially approved prescribing information from three major drug markets - Pfistermeister, Barbara; Saß, Anke; Criegee-Rieck, Manfred; Bürkle, Thomas; Fromm, Martin; Maas, Renke (Clinical Pharmacology & Therapeutics, 2014)
The summary of product characteristics (SPC) should provide information for the safe prescription and use of a drug. We evaluated the consistency of critical interaction warnings, the quality of presentation of undesirable effects as well as concordance of critical information of representative drugs marketed in the United States, the UK, and Germany. Reciprocal warnings regarding drug-drug interactions that constitute contraindications were frequently missing in the SPCs of the drugs concerned (all countries >40%). Most SPCs did not explicitly exclude adverse reactions considered not reasonably attributable to the use of the drug. Comparing SPCs of different generic brands of the same drug, only 60, 10, and 20% of the US, UK, and German SPCs, respectively, provided identical contraindications. Current SPCs contain inconsistencies and misleading data that are not compatible with the purpose of SPCs, which is to provide a basis for the safe prescription and use of drugs.
EVALuna2:129

IT infrastructure components to support clinical care and translational research projects in a comprehensive cancer center - Prokosch, Hans-Ulrich; Ries, Markus; Beyer, Alexander; Schwenk, Martin; Seggewies, Christof; Köpcke, Felix; Mate, Sebastian; Martin, Marcus; Bärthlein, Barbara; Beckmann, Matthias; Stürzl, Michael; Croner, Roland; et al. (User Centred Networked Health Care, 2011)
This paper presents the concept of an integrated IT infrastructure framework established at the comprehensive cancer center at the University Hospital Erlangen. The framework is based on the single source concept where data from the electronic medical record are reused for clinical and translational research projects. The applicability of the approach is illustrated by two case studies from colon cancer and prostate cancer research projects. © 2011 European Federation for Medical Informatics. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.tech.IMMD.infome.itinfr
Keywords: Cancer documentation; Center; Comprehensive cancer; IT infrastructure framework; Single source concept; Translational research

Memorandum on the use of information technology to improve medication safety - Ammenwerth, E.; Aly, A. -F.; Bürkle, Thomas; Christ, P.; Dormann, H.; Friesdorf, W.; Haas, C.; Haefeli, W. E.; Jeske, M.; Kaltschmidt, J.; Menges, K.; Moeller, H.; et al. (Methods of Information in Medicine, 2014)
Information technology in health care has a clear potential to improve the quality and efficiency of health care, especially in the area of medication processes. On the other hand, existing studies show possible adverse effects on patient safety when IT for medication-related processes is developed, introduced or used inappropriately.To summarize definitions and observations on IT usage in pharmacotherapy and to derive recommendations and future research priorities for decision makers and domain experts.This memorandum was developed in a consensus-based iterative process that included workshops and e-mail discussions among 21 experts coordinated by the Drug Information Systems Working Group of the German Society for Medical Informatics, Biometry and Epidemiology (GMDS).The recommendations address, among other things, a stepwise and comprehensive strategy for IT usage in medication processes, the integration of contextual information for alert generation, the involvement of patients, the semantic integration of information resources, usability and adaptability of IT solutions, and the need for their continuous evaluation.Information technology can help to improve medication safety. However, challenges remain regarding access to information, quality of information, and measurable benefits.
EVALuna2:131

Memorandum on the use of information technology to improve medication safety (Memorandum AMTS-IT) Zum Einsatz von Informationstechnologie zur verbesserung der Arzneimitteltherapiesicherheit (Memorandum amts-it) - Aly, Amin Farid; Bürkle, Thomas; Christ, Petra; Dormann, Harald; Friesdorf, Wolfgang; Haas, Christine; Haefeli, Walter E.; Jeske, Martina; Kaltschmidt, Jens; Menges, Klaus; Möller, Horst; Neubert, Antje; et al. (Deutsche Gesellschaft fur Medizinische Informatik, Biometrie und Epidemiologie e.V. (GMDS), 2014)
Information technology in health care has a clear potential to improve quality and efficiency of health care, especially in the area of medication processes. On the other side, existing studies show possible adverse effects on patient safety when IT for medication-related processes is developed, introduced or used inappropriately. The objective of this paper is to summarize definitions and observations on IT usage in pharmacotherapy, and to derive recommendations and future research priorities for decision makers and domain experts. The recommendations address, among others, a stepwise and comprehensive strategy for IT usage in medication processes, the integration of contextual information for alert generation, the involvement of patients, the semantic integration of information resources, usability and adaptability of IT solutions and the need for their continuous evaluation.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Decision support systems; Drug therapy safety; Information technology; Medication safety; Medication safety; Patient safety

The direct costs of adverse drug events in emergency department admissions - Meier, Florian; Maas, Renke; Sonst, Anja; Patapovas, Andrius; Müller, Fabian; Plank-Kiegele, Bettina; Pfistermeister, Barbara; Schöffski, Oliver; Bürkle, Thomas; Dormann, Harald (19. Jahrestagung der Gesellschaft für Arzneimittelanwendungsforschung und Arzneimittelepidemiologie, 2012)
Background: Adverse drug events (ADE) are a health thread for patients and result in rising healthcare costs. Adverse events causing follow-up treatments claim the health insurance funds for prolonged diagnostics and treatment. Several German and international studies confirmed the economic impact, but an internationally accepted and standardized methodical approach to assess the effects has not been established so far. The aim of our study was to derive a portable measurement technique and to analyze the direct costs of community acquired adverse drug events (ADE) in patients with an emergency department (ED) admission and a subsequent hospital stay. Materials and Methods: We conducted a prospective observational study in a 749 bed tertiary care hospital with an annual ED census of more than 40,000 patients. The patient records of all emergencies were systematically analyzed by a team of emergency physicians, clinical pharmacologists and pharmacists for potential ADE. For hospitalized patients with an ADE we calculated the direct costs according to paragraph 21 of the Hospital Remuneration Act (KHEntgG) taking data from the hospital information system (HIS). Results: Among 752 patients we identified 106 patients (mean age: 70.8 years) with an inpatient stay (mean length of stay: 7.5 days) having a total of 153 ADE. This subgroup caused mean costs of 2,968.49 €. Extrapolating these costs for Germany we estimate an amount of € 1.46 bn to be spent for hospitalized patients with ADE annually. Among the patients with ADE cases with cardiovascular disorders and gastrointestinal diseases were dominating. Compared with typical prescription quantities antipsychotic drugs cause frequently ADE and dopaminerge substances lead to extensive hospitalization. The most common drugs associated with ADE were antipsychotics (11.9%), platelet inhibiting factors (10.8%) and ACE blockers (8.7%). Most events were predictable (96.7%), almost 65.4% of the observed ADE were judged to be preventable. Conclusion: Since there is no gold standard for the evaluation of ADE-costs, we recommend the intensive pharmacovigilance method described here in combination with standardized cost data of hospital reimbursement as an appropriate approach for inpatients. ADE were common, often preventable and associated with significant costs. Thus, many stakeholders could benefit from effective and cost efficient prevention strategies for ADE.
UnivIS-Import:2015-03-09:Pub.2012.tech.IMMD.infome.thedir

The effect object paradigm - a means to support medication safety with clinical decision support - Patapovas, Andrius; Pfistermeister, Barbara; Tarkhov, Aleksey; Terfloth, Lothar; Maas, Renke; Fromm, Martin; Kornhuber, Johannes; Prokosch, Hans-Ulrich; Bürkle, Thomas (Studies in health technology and informatics, 2014)
In many countries, officially approved drug information known as summary of product characteristics (SPC) is mostly available in text form, which cannot be used for Clinical Decision Support Systems (CDSS). It may be essential however to substantiate CDSS advice with such legally binding text snippets. In an attempt to link various drug data sources including SPC towards a CDSS to support medication safety in psychiatric patients we arrived at the notion of an effect object.A requirements analysis revealed data items and data structure which are needed from the patient and from the drug information source for the CDSS functionality. Published drug data modelling approaches were analyzed and found unsuitable. A conceptional database modeling approach using top down and bottom up modeling was performed.The schema based data model implemented within the django framework centered on SPC "effect objects" which comprise all SPC data required for the respective CDSS function such as search for contraindications in the proposed medication. Today six effect objects have been defined for contraindications and warnings, missing indications, adverse effects, drug-drug interactions, dosing and pharmacokinetics.The transformation of SPC data to a database-driven "effect objects" structure permits decoupling between the CDSS functions and different underlying data sources and supports the design of reusable, stable and verified CDSS functions.
EVALuna2:127